The Influence of Financial Literacy, Use of Social Media, and Social Demographic Factors on Consumptive Behavior - Muwaffaq, Bahruddin Syah; Dewi, Farida Ratna; Viana, Eka Dasra; Matoati, Rindang (GREENOMIKA, 2023)
This research aims to determine (1) to analyze the level of financial literacy of adolescents in Jabodetabek, (2) to analyze the impact of the dimensions of financial literacy on consumptive behaviour, (3) to analyze the impact of social media usage on the consumptive behaviour,4) analyze the impact of socio-demographic factors the consumptive behaviours type of research is quantitative and qualitative, and the data source is primary data (questionnaire). The method used is descriptive analysis method and analysis of Structural Equation Modemodellingartial Least Square (SEM-PLS). The result is level of financial literacy of the late adolescent is well-literate, with a percentage of 44%. Financial knowledge and socio-demographic factors do not significantly affect delinquent adolescent consumptive behaviour. Financial attitudes, financial behaviour and social media usage significantly impact the late adolescent workforce in Jabodetabek.